Effect of gold dispersion on the photocatalytic activity of mesoporous titania for the vapor-phase oxidation of acetone - Awate, S. V.; Belhekar, Anagha A.; Bhagwat, S. V.; Kumar, R.; Gupta, N. M. (International Journal of Photoenergy, 2008)
Mesostructured titanium dioxide photocatalyst, having uniform crystallite size (6-12 nm) and average pore diameter of similar to 4.2 nm, was synthesized by using a low-temperature nonsurfactant hydrothermal route, employing tartaric acid as a templating agent. Gold additions from 0.5 to 2wt% were incorporated, either during the hydrothermal process or by postsynthesis wet impregnation. Compared to the impregnation-prepared samples, the samples synthesized hydrothermally contained smaller-size (<= 1 nm) gold clusters occluded in the pores of the host matrix. Whereas CO(2) and H(2)O were the main reaction products in UV-assisted vapor-phase oxidation of acetone using these catalysts, C(2)H(6) and HCO(2)CH(3) were also produced for higher acetone concentrations in air. The conversion of acetone was found to increase with decrease in the size of both TiO(2) and gold particles. In situ IR spectroscopy revealed that titania and gold particles serve as independent adsorption and reaction sites for acetone and oxygen molecules. Acetone molecules adsorb exclusively at TiO(2) surface, giving rise to a strongly adsorbed (condensed) state as well as to the formation of formate- and methyl formate- type surface species. Hydroxyl groups at titania surface participate directly in these adsorption steps. Nanosize gold particles, on the other hand, were primarily responsible for the adsorption and activation of oxygen molecules. Mechanistic aspects of the photochemical processes are discussed on the basis of these observations. Copyright (C) 2008.